AutoCAD tutor for engineering graphics : 2013 and beyond - Lang, Kevin (Kevin J.) (Clifton Park, NY : Autodesk Press/Delmar Cengage Learning, 2012)
"A thorough, practical guide featuring self-paced tutorials and a step-by -step approach to help students use and customize AutoCAD to achieve professional results."-- Pg.[4] of cover.
Getting started with AutoCAD -- Drawing setup and organization -- AutoCAD display and basic selection operations -- Modifying your drawings -- Performing geometric constructions -- Working with text, fields, and tables -- Object grips and changing the properties of objects -- Multiview and auxiliary view projections -- Creating section views -- Adding dimensions to your drawing -- Managing dimension styles -- Analyzing 2D drawings -- Creating parametric drawings -- Working with drawing layouts -- Plotting your drawings -- Working with blocks -- Working with attributes -- Working with file references -- Advanced layout techniques -- Solid modeling fundamentals -- Concept modeling, editing solids, and surface modeling -- Creating 2D drawings from a 3D solid model -- Producing renderings and motion studies.
Keywords: AutoCAD; Computer graphics